Identifikasi Pemanfaatan Tanaman Obat Desa Kasiyan Kecamatan Puger sebagai Bahan Penyusun Booklet - Dini Nurmawati; Diah Sudiarti; Haning Hasbiyati (BIOEDUSCIENCE, 2022)
Background: Indonesia is a country that has many types of plants, one of which is medicinal plants, Kasiyan Village is a village located in the Puger district, Jember district, this village grows a lot of plants that are used as medicine by the local community, the purpose of this study is to identify the types of medicinal plants part of the population. as well as how to use it by the people of Kasiyan Village, it is hoped that this can enrich biology learning resources packaged in the form of booklets. Results: There are 47 species of medicinal plants from 25 families that are found in the family Euphorbiaceae. The part of the plant that is widely used is the leaf part with a percentage of 40%. How process plants that are often used is boiled with a percentage of 29%. Conclusions: Medicinal plants have properties that can be used as a treatment of diseases considering the many properties obtained from this medicinal plant for the body not only that this medicinal plant more natural and more efficient.